ChemInform Abstract: Aryne‐Induced Dearomatized Phosphonylation of Electron‐Deficient Azaarenes. Issue 34 (4th August 2016) - Liu, Kai; Liu, Li‐Li; Gu, Cheng‐Zhi; Dai, Bin; He, Lin
Abstract: Azaarenes such as (iso)quinolines, phenanthroline, and acridine are dearomatized via multicomponent reaction with arynes and dialkylphosphites to give corresponding dearomatized phosphonylated heterocycles.